Neonatal monosodium glutamate treatment causes obesity, diabetes, and macrovesicular steatohepatitis with liver nodules in DIAR mice. Issue 9 (September 2014) - Tsuneyama, Koichi; Nishida, Takeshi; Baba, Hayato; Taira, Shu; Fujimoto, Makoto; Nomoto, Kazuhiro; Hayashi, Shinichi; Miwa, Shigeharu; Nakajima, Takahiko; Sutoh, Mitsuko; Oda, Emu; Hokao, Ryoji; et al.
Abstract Background and Aim Non‐alcoholic steatohepatitis (NASH) is the hepatic manifestation of metabolic syndrome (MS). Monosodium glutamate (MSG)‐treated ICR mice is a useful model of MS and NASH, but it shows the different patterns of steatosis from human NASH. Because inbred aged DIAR (ddY, Institute for Animal Reproduction) mice spontaneously show the similar pattern of steatosis as NASH, we analyzed their liver pathology after administering MSG. Methods MSG‐treated DIAR mice (DIAR‐MSG) and untreated DIAR mice (DIAR‐controls) were sacrificed and assessed histopathologically at 29, 32, 40, 48, and 54 weeks of age. The NASH activity score, body mass index, blood glucose level, and oral glucose tolerance test were also assessed. Results The body mass index and blood glucose levels of DIAR‐MSG were significantly higher than controls. The oral glucose tolerance test revealed a type 2 diabetes pattern in DIAR‐MSG. The livers of DIAR‐MSG mice showed macrovesicular steatosis, lobular inflammation with neutrophils, and ballooning degeneration after 29 weeks. At 54 weeks, mild fibrosis was observed in 5/6 DIAR‐MSG and 2/5 DIAR‐control mice. In imaging mass spectrometry analysis, cholesterol as well as triglyceride accumulated in the liver of DIAR‐MSG mice. Atypical liver nodules were also observed after 32 weeks in DIAR‐MSG, some with cellular and structural atypia mimicking human hepatocellular carcinoma. The NASH activity score of DIAR‐MSG after 29 weeks was higher than that of control mice, suggesting the development of NASH. Conclusions DIAR‐MSG had NASH‐like liver pathology and liver nodules typically associated with MS symptoms. DIAR‐MSG provides a valuable animal model to analyze NASH pathogenesis and carcinogenesis.